Variáveis preditoras da disposição de jovens para ajudar pessoas em risco de suicídio - Bezerra, Viviane Alves dos Santos (2021)
This research aimed to adapt and validate the Suicide Helpfulness Scale - SHS for the Brazilian context through two studies. Study 1 had the participation of 206 students, with an average age of 16.73. They responded to SHS and sociodemographic questions. The results supported the original four-factor model and it was found a total Composite Reliability of 0.90. Study 2, which has a confirmatory nature, had the participation of 212 students, predominantly female (58%) and with an average age of 16.67. Three models were tested and the results corroborated with the adequacy of the tetrafactorial structure, observing meritorious adjustment indicators. Thus, it is concluded that the SHS has psychometric characteristics suitable for the Brazilian context. It can also be used in research that investigates how much young people are willing to help persons who is at risk of suicide.